A Role for Phosphoinositides in Regulating Plant Nuclear Functions - Dieck, Catherine B.; Boss, Wendy F.; Perera, Imara Y. (Frontiers in Plant Science, 2012)
Nuclear localized inositol phospholipids and inositol phosphates are important for regulating many essential processes in animal and yeast cells such as DNA replication, recombination, RNA processing, mRNA export and cell cycle progression. An overview of the current literature indicates the presence of a plant nuclear phosphoinositide (PI) pathway. Inositol phospholipids, inositol phosphates, and enzymes of the PI pathway have been identified in plant nuclei and are implicated in DNA replication, chromatin remodeling, stress responses and hormone signaling. In this review, the potential functions of the nuclear PI pathway in plants are discussed within the context of the animal and yeast literature. It is anticipated that future research will help shed light on the functional significance of the nuclear PI pathway in plants.